2018
DOI: 10.1186/s12950-018-0200-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of hyperexcitability of trigeminal nociceptive neurons associated with inflammatory hyperalgesia following systemic administration of lutein via inhibition of cyclooxygenase-2 cascade signaling

Abstract: IntroductionLutein is a dietary constituent known to inhibit inflammation; however, its effect on nociceptive neuron-associated hyperalgesia remains to be determined. The present study therefore investigated under in vivo conditions whether administration of lutein attenuates the inflammation-induced hyperexcitability of trigeminal spinal nucleus caudalis (SpVc) neurons that is associated with mechanical hyperalgesia.ResultsComplete Freund’s adjuvant (CFA) was injected into the whisker pads of rats to induce i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 43 publications
7
26
0
Order By: Relevance
“…Our present findings also agree with a previous report showing that 6 h after pretreatment with the polyphenol, resveratrol, there is a significant decrease in the mean thickness of inflammation‐induced edema in the whisker pad, compared with untreated, inflamed rats, and also a significant decrease in the number of c‐Fos‐immunoreactive SpVc and C1 neurons in inflamed rats compared with naïve rats . We have also previously observed the following findings in a CFA‐induced chronic inflammatory pain model: (i) the mechanical threshold is significantly lower in inflamed rats than in uninjected naïve rats, and this low threshold returns to control levels by 3 d after administration of lutein; (ii) lutein administration causes the inflammation‐induced edema to return to control levels; and (iii) the increased mean number of COX‐2‐immunoreactive cells in the whisker pads of inflamed rats also returns to control levels after administration of lutein . In this study, the same concentration of lutein (10 mg kg −1 , administered intraperitoneally) that attenuates CFA inflammation‐induced chronic inflammatory hyperalgesia also inhibited acute inflammatory responses.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our present findings also agree with a previous report showing that 6 h after pretreatment with the polyphenol, resveratrol, there is a significant decrease in the mean thickness of inflammation‐induced edema in the whisker pad, compared with untreated, inflamed rats, and also a significant decrease in the number of c‐Fos‐immunoreactive SpVc and C1 neurons in inflamed rats compared with naïve rats . We have also previously observed the following findings in a CFA‐induced chronic inflammatory pain model: (i) the mechanical threshold is significantly lower in inflamed rats than in uninjected naïve rats, and this low threshold returns to control levels by 3 d after administration of lutein; (ii) lutein administration causes the inflammation‐induced edema to return to control levels; and (iii) the increased mean number of COX‐2‐immunoreactive cells in the whisker pads of inflamed rats also returns to control levels after administration of lutein . In this study, the same concentration of lutein (10 mg kg −1 , administered intraperitoneally) that attenuates CFA inflammation‐induced chronic inflammatory hyperalgesia also inhibited acute inflammatory responses.…”
Section: Discussionsupporting
confidence: 93%
“…We have also previously observed the following findings in a CFA‐induced chronic inflammatory pain model: (i) the mechanical threshold is significantly lower in inflamed rats than in uninjected naïve rats, and this low threshold returns to control levels by 3 d after administration of lutein; (ii) lutein administration causes the inflammation‐induced edema to return to control levels; and (iii) the increased mean number of COX‐2‐immunoreactive cells in the whisker pads of inflamed rats also returns to control levels after administration of lutein . In this study, the same concentration of lutein (10 mg kg −1 , administered intraperitoneally) that attenuates CFA inflammation‐induced chronic inflammatory hyperalgesia also inhibited acute inflammatory responses. Therefore, taken together, these findings suggest that the acute systemic administration of lutein can attenuate the acute inflammation‐induced neuronal activity of trigeminal spatial distribution in the SpVc and C1 dorsal horn via suppression of COX‐2 signaling pathways, in addition to its effects on chronic inflammation.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The present authors recently tested the hypothesis that intraperitoneally administered dietary constituents could attenuate SpVc neuronal hypersensitivity related to mechanical hyperalgesia induced by complete Freund's adjuvant (CFA) [62,63]. In addition, the authors showed that resveratrol, DHA, and lutein provided in the diet inhibited inflammatory mechanical hyperalgesia and associated nociceptive neuronal hyperexcitability induced by CFA, possibly by inhibiting the Cox-2 converting enzyme from arachidonic acid to PGE 2 [64][65][66]. This experimental series showed (i) that the lowered escape threshold for mechanical stimulation in inflamed rats returned to control levels with ongoing administration of dietary constituents, (ii) that dietary components also reversed the high-frequency SpVc WDR discharges elicited by mechanical non-noxious and noxious stimuli, (iii) that dietary constituents returned the spontaneous discharges rates of SpVc WDR neurons as well as the noxious pinch-evoked after-discharge frequency in inflamed rats, and (iv) that control levels of receptive field expansion in inflamed rats were attained [64][65][66].…”
Section: How Do Dietary Constituents Mechanistically Modulate Inflammmentioning
confidence: 97%